Synergistic Effect of Mesoporous Silica and Hydroxyapatite in Loaded Poly(DL-lactic-co-glycolic acid) Microspheres on the Regeneration of Bone Defects. (29th August 2016) - He, Shu; Lin, Kai-Feng; Fan, Jun-Jun; Hu, Gang; Dong, Xin; Zhao, Yi-Nan; Song, Yue; Guo, Zhong-Shang; Bi, Long; Liu, Jian
Abstract : A microsphere composite made of poly(DL-lactic-co-glycolic acid) (PLGA), mesoporous silica nanoparticle (MSN), and nanohydroxyapatite (nHA) (PLGA-MSN/nHA) was prepared and evaluated as bone tissue engineering materials. The objective of this study was to investigate the synergistic effect of MSN/nHA on biocompatibility as well as its potential ability for bone formation. First, we found that this PLGA-MSN/nHA composite performed good characteristics on microstructure, mechanical strength, and wettability. By cell culture experiments, the adhesion and proliferation rate of the cells seeded on PLGA-MSN/nHA composite was higher than those of the controls and high levels of osteogenetic factors such as ALP and Runx-2 were detected by reverse transcriptase polymerase chain reaction. Finally, this PLGA-MSN/nHA composite was implanted into the femur bone defect in a rabbit model, and its ability to induce bone regeneration was observed by histological examinations. Twelve weeks after implantation, the bone defects had significantly more formation of mature bone and less residual materials than in the controls. These results demonstrate that this PLGA-MSN/nHA composite, introducing both MSN and nHA into PLGA microspheres, can improve the biocompatibility and osteoinductivity of composite in vitro and in vivo and had potential application in bone regeneration.